Voice over IP Forensic Approaches: A Review - Al-Saadawi, Hussein; Varol, Asaf (Ieee, 2017)
Voice over Internet Protocol (VoIP) is one of the highly used applications for voice and data communication purposes. The convenience of using VoIP applications, its acceptable quality, and the relatively low cost of usage have made it a potential replacement for landline and cellular communication. Along with these advantages, the vulnerability of using VoIP is usually considered the most cumbersome con. Various researchers have investigated VoIP risk issues; yet, a very limited research has approached VoIP from digital forensic perspective. A survey of the prominent research proposals and methods that presented VoIP forensic within their context is provided in this paper. In addition, a contemporary discussion on trends for improving VoIP forensic is given in this paper to formulate directions for new and useful research in the area of VoIP forensic.
5th International Symposium on Digital Forensic and Security (ISDFS) -- APR 26-28, 2017 -- Tirgu Mures, ROMANIA
Keywords: VoIP; digital forensic; VoIP protocols; VoIP vulnerabilities; research trends